Metaphor and the portrayal of the cause(s) of sin and evil in the Gospel of Matthew - Stack, Judith V. (Biblical interpretation series, 2020)
"Metaphor and the Portrayal of the Cause(s) of Sin and Evil in the Gospel of Matthew traces the range and significance of metaphors used in Matthew for the origin and sin and evil and their congruence with key texts of the Second Temple milieu. While traditional theology has often sought to pinpoint a single cause of sin and evil, Matthew's use of a spectrum of metaphors undermines theologically reductionist approaches and opens up a rich range of ways for conceiving of and talking about the cause of sin and evil. Ultimately, the use of metaphor (necessary to discussions of sin) destabilizes foundationalist theologies of sin, and any theology of sin must grapple with the inherently tensive nature of metaphorical language"--